2012
DOI: 10.1063/1.4729730
|View full text |Cite
|
Sign up to set email alerts
|

The effect of applied electric field on pulsed radio frequency and pulsed direct current plasma jet array

Abstract: Here we compare the plasma plume propagation characteristics of a 3-channel pulsed RF plasma jet array and those of the same device operated by a pulsed dc source. For the pulsed-RF jet array, numerous long life time ions and metastables accumulated in the plasma channel make the plasma plume respond quickly to applied electric field. Its structure similar as “plasma bullet” is an anode glow indeed. For the pulsed dc plasma jet array, the strong electric field in the vicinity of the tube is the reason for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…The ionization rate shown in Figure 2 1) and (5). The high concentration of air at the nozzle results in localized photoionization, which cannot act as a source of pre-ionization and provide enough electrons ahead of the streamer head.…”
Section: Results and Analysismentioning
confidence: 97%
“…The ionization rate shown in Figure 2 1) and (5). The high concentration of air at the nozzle results in localized photoionization, which cannot act as a source of pre-ionization and provide enough electrons ahead of the streamer head.…”
Section: Results and Analysismentioning
confidence: 97%
“…[11] Recently, several groups claimed experimentally that pulse-modulation of the rf power could significantly change the gas temperature (T g ). [12][13][14] Theoretical models simulating T g for a self-consistent, non-equilibrium plasma discharge have been developed over the last 50 years. Pytte and Winsor [15] gave a simple twotemperature theoretical model for atmospheric helium arc plasma in a cylindrical duct.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, efforts to improve the downstream uniformity of jet arrays have mainly centered on optimizing voltage source electrical parameters and the gas medium flow rate, adding current-limiting devices, and addition of small amounts of electronegative gas. Cao et al [18] reported that voltage frequency significantly affects the downstream uniformity of 2-D arrays; Hu et al [19] designed a 2-D jet array with three jets driven by a radio-frequency pulse and direct-current pulse voltage to generate parallel plumes beams and divergent plume beams, respectively. Fan et al [20] found that the conduction current of a singleelectrode configuration array decreases as gas flow rate increases, which drives down the repulsion between jets.…”
Section: Introductionmentioning
confidence: 99%